Strategi Telemarketing yang Etis: Pendekatan Pemasaran Berbasis Prinsip Islam - Nurriza Sofiastuti; Sulistyowati Sulistyowati (Jurnal Publikasi Manajemen Informatika, 2025)
Telemarketing is a modern marketing strategy that relies on long-distance communication to offer products or services. This strategy offers several advantages, including cost efficiency, two-way communication, and the ability to reach consumers personally. However, telemarketing also poses ethical challenges such as privacy violations, misuse of data, and the risk of manipulation in communication. From an Islamic perspective, Shariah-compliant telemarketing should prioritize the values of honesty (ṣidq), transparency (bayān), and non-coercion (ikhtiyar). The purpose of this study is to examine how telemarketing can be ethically applied in accordance with Islamic principles to create transactions that are fair, efficient, and spiritually and socially beneficial. This study was conducted through literature analysis related to marketing strategies, Islamic business ethics, and telemarketing practices. The results show that the implementation of Islamic telemarketing has the potential not only to increase marketing effectiveness, but also to become a means of da'wah in promoting Shari'ah values. This conclusion reinforces the importance of integrating ethical values into any business strategy to ensure the achievement of maslahat for all parties involved.